2021
DOI: 10.1177/00469580211067477
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Adherence to Anti-diabetic Medications and Associated Factors in Mizan-Tepi University Teaching Hospital: A Cross-Sectional Study

Abstract: Introduction: A number of medications have been demonstrated to lower blood glucose. However, current-day management has failed to achieve and maintain the optimal glycemic level for diabetic patients. Patients’ non-adherence is among the most contributing factors. Therefore, the aim of this study was to explore the prevalence of non-adherence to anti-diabetic medications and associated factors. Methods: A hospital based cross-sectional study was conducted from November 2020 to January 2021. A systematic rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 28 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…Jafer Siraj et al ,[ 10 ] a cross-sectional study, conducted at Mizan-Tepi University Teaching Hospital, Mizan-aman, Ethiopia, also reported the similar reasons for nonadherence to the present study such as financial problems, forgetfulness, and overlapping schedule of medication intake with working time and side effects of medications. The financial problem was the major contributor which led to nonadherence, which was faced especially by the elderly and widowed patients because of their inability to earn money.…”
Section: Discussionsupporting
confidence: 74%
“…Jafer Siraj et al ,[ 10 ] a cross-sectional study, conducted at Mizan-Tepi University Teaching Hospital, Mizan-aman, Ethiopia, also reported the similar reasons for nonadherence to the present study such as financial problems, forgetfulness, and overlapping schedule of medication intake with working time and side effects of medications. The financial problem was the major contributor which led to nonadherence, which was faced especially by the elderly and widowed patients because of their inability to earn money.…”
Section: Discussionsupporting
confidence: 74%
“…Additionally, patients with Bachelor’s and Master’s degrees had good adherence rates of 87.80% and 88.88%, respectively. This, when compared to a study conducted by Siraj et al, found higher adherence rates among patients with Bachelor’s and Master’s degrees [ 16 ]. Adherence rates could vary among patients with different levels of education.…”
Section: Discussioncontrasting
confidence: 61%
“…The sample size was determined using the formula for the proportion of the single population considering the proportion of medication adherence of 68% in Ethiopia ( 19 ) with a precision level of 5 and 15% for non-response and a design effect of 1.5, resulting in 552 subjects. Diabetic subjects aged ≥18 years who had been followed for more than three months were included in the study.…”
Section: Methodsmentioning
confidence: 99%